2017
DOI: 10.1186/s13075-017-1255-7
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and the risk of primary Sjögren’s syndrome: a nested case control study

Abstract: BackgroundSmoking is reported to affect the risk of a number of chronic disorders, including rheumatic diseases. Previous cross-sectional studies have shown a lower frequency of smoking in patients with primary Sjögren’s syndrome (pSS). The aim of this study was to investigate the impact of smoking and socioeconomic status on the risk of subsequent diagnosis of pSS in a nested case-control study.MethodParticipants in two large population-based health surveys who were later diagnosed with pSS were identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
3
26
1
Order By: Relevance
“…Finally, we were unable to account for several potential confounding factors influencing the risk of developing pSS. For instance, we had no records on cigarette smoking which is implicated in the pathogenesis of SLE and rheumatoid arthritis [29,46], although current reports with regard to risk for pSS are conflicting [15][16][17][18][19][20]. Moreover, drugs may induce autoimmune disease, including pSS [47,48], an eventual effect we did not account for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we were unable to account for several potential confounding factors influencing the risk of developing pSS. For instance, we had no records on cigarette smoking which is implicated in the pathogenesis of SLE and rheumatoid arthritis [29,46], although current reports with regard to risk for pSS are conflicting [15][16][17][18][19][20]. Moreover, drugs may induce autoimmune disease, including pSS [47,48], an eventual effect we did not account for.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, there is still little known about environmental risk factors in pSS. One study found associations between occupational exposure to solvents and pSS [14], and a few studies have assessed smoking in pSS, however yielding partly conflicting results [15][16][17][18][19][20]. Notably, a link between infections and pSS has repeatedly been proposed, with both viruses and bacteria suggested as potential triggers for pSS development [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…An intuitive explanation for these observations is that the oral, respiratory and ocular irritation caused by tobacco smoke makes patients with SS more likely to discontinue smoking. However, intriguingly, two studies have reported lower prevalence of focal sialadenitis in minor salivary gland biopsies from smoking compared to nonsmoking patients with SS . Lower inflammatory activity with lesser leucocyte infiltration in salivary glands could at least hypothetically be linked to a lower prevalence of SS amongst smokers.…”
Section: Organic Chemical Factorsmentioning
confidence: 98%
“…A possible explanation of the lower frequency of current smokers amongst pSS patients could be that the dryness of the oral cavity and airways increases the irritation of the smoke thereby making the patients more prone to quit smoking. Although the symptoms of dryness may have impact, one study comparing pSS patients with non-pSS sicca patients [9] and another study using data on smoking acquired years before the individuals were diagnosed with pSS [8] still found a lower frequency of current smokers amongst pSS patients which may indicate that dryness might not be the only explanation. In the current study, we investigated whether smoking habits is associated with the phenotypic expression of pSS.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the presence of the IFN signature has been associated with lower patient-reported symptoms as evaluated by the EULAR Sjögren's syndrome patient-reported index (ESS-PRI) [5]. We recently published an epidemiological study showing that smoking was associated with a lower risk of later being diagnosed with pSS [8]. Similar findings have also been reported by others reporting a lower prevalence of smokers amongst pSS patients [9][10][11], and lower frequency of focal sialoadenitis [9,11] and seropositivity for anti-SSA antibodies [9,11] amongst smoking pSS patients.…”
Section: Introductionmentioning
confidence: 99%